CERMIN WANITA DI MATA DOMINASI MASYARAKAT PATRIARKAT DALAM PEREMPUAN SUCI DAN PEREMPUAN TERLUKA KARYA QAISHRA SHAHRAZ - Mamba`ul Athiyyah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
Perempuan Suci (Holy Woman) and Perempuan terluka (Typhoon) are written by Qaishra Shahraz —a Pakistanian female writer. The novels talk about Woman and Freedom. This paper aims to discuss on how Qaishra Shahraz’s view on woman and freedom, how the tradition and culture subordinates woman. With the theory of Foucault about the power and the theory of feminist, this paper observes the character of Qaishra Shahraz, besides her novels. After seeing her view, it is found that Qaishra Shahraz successfully makes the world see the other side of the Pakistanian women. Qaishra Shahraz has never declared herself as feminist.